Maximum‐revenue tariffs versus free trade. (11th April 2020) - Collie, David R.
Abstract: Welfare with the maximum‐revenue tariff is compared to free‐trade welfare under Cournot duopoly with differentiated products; under Bertrand duopoly with differentiated products; and under perfect competition in the case of a large country able to affect its terms of trade. Under Cournot duopoly and Bertrand duopoly, assuming linear demands and constant marginal costs, welfare with the maximum‐revenue tariff is always higher than free‐trade welfare. Under perfect competition, assuming linear demand and supply, welfare with the maximum‐revenue tariff will be higher than free‐trade welfare if the country has sufficient market power.